Human trafficking policy implementation: A case study of Malaysia / Wan Nur Ibtisam Wan Ismail - Wan Ismail, Wan Nur Ibtisam (2014)

(untitled)
Human trafficking is a complex global crime that exploits women, men and children. Due to the seriousness of the crime, Malaysia enacted the Anti-Trafficking in Persons and Anti-Smuggling of Migrants Act in 2007. Despite considering human trafficking to be a priority area for action through the enactment of the 2007 Act, Malaysia is still struggling in translating the intent of the policy into actual implementation. Hence, the study attempts to provide an understanding of human trafficking in Malaysia through the policy implementation lens. It analyses how human trafficking policy is being translated by bureaucratic implementers into action. The study adopts a combination of qualitative research methods – semi-structured individual and focus group interviews, field observations and written documents – to illustrate human trafficking policy implementation in Malaysia. The target population of the study is government bureaucrats who are involved in implementing human trafficking policy in Malaysia. For the study, 15 government bureaucrats were interviewed regarding their experience on human trafficking policy implementation. To provide multiple perspectives to the study, it also incorporates non-governmental organisations (NGOs) and trafficked victims as participants. Six NGO representatives and five male trafficked victims were interviewed. Three focus group interviews based on different categories of victims were also conducted, which consist of 49 female trafficked victims at selected shelter homes. There is a dearth of knowledge on human trafficking in Malaysia particularly on policy implementation. Hence, this study contributes to the body of knowledge on human trafficking and the body of work on implementation research. Using the policy implementation lens, the study explores human trafficking phenomenon in Malaysia through four theoretical underpinnings: theory of bureaucracy, implementation study, iv inter-organisational coordination and street-level bureaucracy. The 2007 Act becomes the country‟s primary policy that provides for the offence of trafficking in persons, the victims‟ protection and support, and the establishment of Council for Anti-Trafficking in Persons and Anti-Smuggling of Migrants (MAPO). To ensure effective implementation of the legal mechanisms outlined in the 2007 Act, the government formulated the National Action Plan against Trafficking in Persons (2010-2015) as a guideline to the national initiative in combating human trafficking. The empirical study identifies seven emerging themes that influence the implementation process of translating the policy intent into actual practice: incomprehensive coordination; incompatible resources; criminal approach; critical information flows; hierarchical control; low discretion; and paradigm shift imperative. These themes emerge through the analysis of research findings against the backdrop of the theoretical underpinnings and past studies. This study indicates the need to address these factors that critically influence human trafficking policy implementation in Malaysia. Understanding the complexity of human trafficking policy implementation entails the development of pragmatic recommendations towards abating the crime.